Characterization of Streptococcus pneumoniae TrmD, a tRNA Methyltransferase Essential for Growth - O'Dwyer, Karen (American Society for Microbiology, 2004)
Down-regulation of expression of trmD, encoding the enzyme tRNA (guanosine-1)-methyltransferase, has shown that this gene is essential for growth of Streptococcus pneumoniae. The S. pneumoniae trmD gene has been isolated and expressed in Escherichia coli by using a His-tagged T7 expression vector. Recombinant protein has been purified, and its catalytic and physical properties have been characterized. The native enzyme displays a molecular mass of approximately 65,000 Da, suggesting that streptococcal TrmD is a dimer of two identical subunits. In fact, this characteristic can be extended to several other TrmD orthologs, including E. coli TrmD. Kinetic studies show that the streptococcal enzyme utilizes a sequential mechanism. Binding of tRNA by gel mobility shift assays gives a dissociation constant of 22 nM for one of its substrates, [Formula: see text]. Other heterologous nonsubstrate tRNA species, like [Formula: see text] , tRNA(Phe), and [Formula: see text] , bind the enzyme with similar affinities, suggesting that tRNA specificity is achieved via a postbinding event(s).